A COMPREHENSIVE REVIEW ON THE GENUS PLUMBAGO WITH FOCUS ON PLUMBAGO AURICULATA (PLUMBAGINACEAE) - Singh, Karishma; Naidoo, Yougasphree; Baijnath, Himansu (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The genus Plumbago distributed in warm tropical regions throughout the world is the largest genus in Plumbaginaceae. Medicinal plants are characteristic to the genus Plumbago and are cultivated and utilized worldwide. Plumbago auriculata Lam. is common in South Africa and is often cultivated for its ornamental and medicinal uses throughout the world. Materials and Methods: A comprehensive review of the genus Plumbago with focus on Plumbago auriculata was carried out and information was gathered using scientific publications, conference proceedings, the internet and books. Articles based on the morphology, pharmacological and medicinal uses of Plumbago auriculata was analysed thoroughly. Results: Plumbago auriculata plant parts posses a wide range of phytochemicals with plumbagin being the marker compound showing various pharmacological activities. Different plant parts are claimed to be used for the treatment of human and animal ailments, however they do exhibit toxic properties and need to be administered with caution. Salt secreting glands and trichomes are characteristic of Plumbaginaceae. Conclusion: This study reveals new insights on the genus Plumbago and the potential use of species in the genus as medicinal plants. Plumbago auriculata possess the bioactive compound plumbagin and secondary metabolites, thus, it is of high medicinal importance. P. auriculata is a poorly nor favourite studied species in the genus Plumbago and further research needs to be carried out to explore specific details of the species.